Water wave diffraction by a cylinder array. Part 2. Irregular waves - Ohl, C; Taylor, P; Eatock Taylor, R; Borthwick, A (Cambridge University Press, 2001)
Diffraction of irregular waves, focused wave groups, and random seas by an array of vertical bottom-mounted circular cylinders is investigated using theoretical, computational and experimental methods. This is an extension of our study of such an array in regular waves, reported in Part 1. Linear focused wave group theory is reviewed as a method for predicting the probable shape of extreme events from random wave spectra. Measurements are presented of the free surface elevation distribution in the vicinity of a multi-column structure in an offshore basin when subjected to irregular waves having peak frequencies and significant wave heights in the range 0.449 < kpa < 0.555 and 0.114 < Hs < 0.124 respectively, where a is the cylinder radius. Analytical linear diffraction theory is extended for application to focused wave groups and random seas. Experimental irregular wave data are analysed for comparison with this theory. Linear diffraction theory for random seas is shown to give an excellent prediction of incident wave spectral diffraction, while linear diffraction theory for focused wave groups works well for linearized extreme events. Due to the phase shifting of incident wave spectral components, diffraction is shown to generate focused wave groups in the vicinity of the cylinder array.